Analysis of Lag Behind Thyrotropin State After Radioiodine Therapy in Hyperthyroid Patients - Mokaddema, Mohshi Um; Begum, Fatima; Salekin, Simoon; Naushin, Tanzina; Quddus, Sharmin; Ali, Nabeel Fahmi; Sultana, Sadia; Nahar, Nurun (Bangladesh Journal of Nuclear Medicine, 2016)
Introduction: A good number of hyperthyroid patients may show delayed recovery of Thyroid Stimulating Hormone (TSH) level in clinically evident euthyroid condition after radioiodine therapy. This group of patients need to be addressed in therapeutic decision making. The purpose of the study was to evaluate the duration and pattern of lag in TSH recovery after I - 131 therapy and the relationship between clinical parameters with stable thyroid function status. Materials and Methods: Total 192 hyperthyroid patients treated with I-131 were included in this study. These patients were followed up clinically and biochemically at three month, six month and one year after radioiodine therapy. Patients having suppressed TSH with normal Free Triiodothyronine (FT3) / Free Thyroxin (FT4) level and clinically euthyroid condition were followed-up for one year without giving antithyroid drug. Results: At three months follow-up 42/192 (22%) had suppressed TSH with normal FT3/FT4 level. Duration of lagging behind state of TSH was three months for 42 patients (22 %), six months for 13 patients (7%) and One year in three patients (2 %). Twelve patients were lost from follow-up. Among 30 patients with lag behind TSH level, 16 (53%) became hypothyroid, 8 (27%) became euthyroid and 6 (20%) became hyperthyroid at one year follow-up. Lagging behind patient with high serum FT4 level at diagnosis and high Radio Active Iodine Uptake (RAIU) showed increased rate of relapse of hyperthyroidism. Conclusion: Lagging state of TSH may be unexpectedly prolonged in some hyperthyroid patients treated with I-131. These patients should be followed up with both TSH and thyroid hormone levels. Most of them do not require further therapy with short period of time. Bangladesh J. Nuclear Med. 17(2): 103-107, July 2014